The socio-economic impact of drought in the period 1924-1934 on the magisterial district of Vanrhynsdorp - Rademan, Daniel Johannes Rouxan (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.